ULAR TANGGA KARIER SEBAGAI MEDIA LAYANAN BIMBINGAN KARIER UNTUK SISWA SEKOLAH DASAR - Putu Agus Indrawan; Suriata Suriata (Universitas Borneo Tarakan, 2021)
ABSTRACTThe purpose of this research is to create a simulation game Snakes and Ladders Career which is used by Guidance and Counseling teachers to develop insight and career readiness of elementary school students. The steps of this research development are (1) preparation, (2) preparation of the initial product, (3) expert test, (4) revision of the first product, 5) field test, and 6) revision of the final product. The product trial was conducted on 9 users and 2 experts. The resulting product specifications are in the form of a snake and ladder graphic media with a size of 3x3 m and dice size 20x20x20 cm as well as a guide book. The game media